Kajian Pengaruh Predisposing, Enabling Dan Reinforcing Factors Terhadap Praktek Kerja Tenaga Kerja Bongkar Muat Yang Berisiko Terjadinya Kecelakaan Kerja Di Pelabuhan Tanjung Emas Semarang - Rais, Muhammad; Prabamurti, Priyadi Nugraha; Widjasena, Baju (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: Occupational Health and Safety aims to prevent, reduce and eliminate accidents. By the year of 2007, number of loading-unloading laborers in Tanjung Emas Port reach 756 persons, 2.56% of them experienced working accidents in the last 4 years. This research isaimed to analyze predisposing, enabling and reinforcing factors influencing loading-unloading laborers risky working behavior at Tanjung Emas Semarang.Method: It was a cross sectional study of 90 respondents from 756 laborers. Proportional random sampling was employed to obtain number of samples required. Data were collected using check list and questionnaires and were analyzed with logistic regression.Result: This study revealed that laborers’ knowledge and attitudes, equipments, working standard, support of the head of laborers’ group and laborers’ cooperation generally categorized as good. Laborers’ knowledge of occupational health and safety, equipment availability, working standard, equipment design, support of head of laborers’ group andsupport laborers’ cooperation were correlated with laborers’ working practice. Knowledge and support of laborers’ cooperation were simultaneously correlated to laborers’ working practice.Keywords : predisposing, enabling, reinforcing, risky behavior, working accident